Birth gap and the recurrence risk of autism spectrum disorders: A population-based cohort study. (September 2015) - Beenstock, Michael; Raz, Raanan; Levine, Hagai
Highlights: ASD recurrence rate was 5.3% among younger siblings. We found that short birth gaps increase ASD recurrence risk. This association was independent of birth order, sex, paternal ages and ethnicity. Recurrence risk varies inversely with birth order. Abstract: Population-based data on the magnitude and determinants of Autism Spectrum Disorder (ASD) recurrence risk in families with an index case are rare. We examined whether short birth gaps and other birth spacing factors increase the risk of recurrence, using a population-based cohort study in Israel. We examined records of younger siblings of index cases (children diagnosed with ASD), and estimated recurrence risk and its determinants. Overall, 5.25% (261/4976) of younger siblings were diagnosed with ASD. Younger siblings with birth gaps less than two years of their index case had significantly higher risk compared to the rest (odds ratio = 1.66, 95% CI 1.25–2.22). The association remained significant in models adjusted for sex of the index cases and their younger siblings, ethnicity, parental ages and birth order (odds ratio = 1.43, CI 1.03–1.96). This finding suggests that short birth gaps from the index case increase the risk of ASD among younger siblings.